Aves migratorias en los humedales de los alrededores de Mohena Caño, Cantagallo y desembocadura del río Itaya en época de vaciante, Loreto - García Solsol, Luis Armando (2022)
From August to October 2020, observations were conducted to identify the migratory bird species frequenting the wetlands around Mohena caño, Cantagallo and Itaya River mouth during emptying season, using linear transect and canoe census methods. Considering the three sampling sites, a richness of 7 orders with 15 families and 34 species of migratory birds is reported considering the 3 sampling sites. The distribution of the random migratory birds were Actitis macularis, Falco Peregrinus, Myiodinastes luteiventris, Pandion haliaetus, Piranga rubra, Sicialis flaveola, Tyrannus albogularis, Solitary Tringa, Tyrannus tyrannus, Vanellus kaenus, Bartramia longicauda, Calidris fuscicollis, Calidris himantoguapus, Ciconia , Callidris minutilla, Hymanthopus mexicanus, Pyrocephalus rubinus, Tringa flavipes and Tringa melanoleuca; and the least amount of the grouped type the species were, Calidris melanotos, Calidris subruficcollis, Vireo olivaceus, Dendrocygna autumnalis, Himantopus melanurus, Hirundo rustica, Leistes militaris, Progne elegans, Rynchops niger, Sporophila bouvronides, Sporophila lineola, Vanellus chilensis and Egretta caerulea. The highest relative abundance corresponded to Sporophila lineola (4.43 ind/km2) and the highest densities were obtained by Sporophila lineola (56.62 ind/km2,) Calidris melanotos (14.85 ind/km2) and Charadius collaris (9.39 ind/km2). km2). It is concluded that according to the distribution, the largest number of species belonged to the random and clustered type.